Effects of follicular phase exercise on luteinizing hormone pulse characteristics in sedentary eumenorrhoeic women - Williams, N I; McArthur, J W; Turnbull, B A; Bullen, B A; Skrinar, G S; Beitins, I Z; Besser, G M; Rees, L H; Gilbert, I; Cramer, D (Clinical endocrinology (Oxford), 1994)
Current studies reveal little regarding the inception of exercise-induced LH changes during physical training. This study aimed to assess the susceptibility of the hypothalamic-pituitary axis to the acute physical stress of exercise in untrained, physically inactive women. The acute effects of submaximal endurance exercise upon the pulsatile LH secretion in the follicular phase were compared with those accompanying leisurely strolling for a similar time period. All subjects were eumenorrhoeic, as determined by biphasic temperature patterns, detection of the urinary LH surge, and mid-luteal serum progesterone levels. Subjects were not physically active and had little history of strenuous exercise (VO2max = 38.0 +/- 1.8) (mean +/- SEM) ml/kg/min). All women completed a 13.5-hour pulsatility test which included three consecutive 20-minute runs on a treadmill at 50, 60 and 70% of the subjects' maximum oxygen uptake (n = 16). Six of these same subjects completed a separate test on another occasion in which one hour of leisurely strolling was substituted for exercise. Blood was sampled every 10 minutes via an indwelling cannula for 4.5 hours before and 8 hours after one hour of exercise and or strolling. A pulse algorithm (Pulsar) was used to quantify LH pulse characteristics. Exercise produced no significant effects upon LH pulse frequency or mean serum LH concentration. However, exercise of moderate intensity caused a significant increase in LH pulse amplitude (P < 0.05). Strolling produced no significant changes in LH secretion. Acute exercise of moderate intensity in the follicular phase of untrained women is an insufficient stimulus to inhibit the GnRH pulse generator in the post-exercise period, yet may produce a slight stimulatory effect on the amount of LH released per pulse.